Preassembled complexes of hAgo2 and ssRNA delivered by nanoparticles: a novel silencing gene expression approach overcoming the absence of the canonical pathway of siRNA processing in the apicomplexan parasite Babesia microti, blood parasite of veterinary and zoonotic importance - Shimaa A. E-S. El-Sayed; Mohamed A. Rizk; Hang Li; Uday Kumar Mohanta; Iqra Zafar; Shengwei Ji; Zhuowei Ma; Thom Do; Yongchang Li; Daisuke Kondoh; Jerzy Jaroszewski; Xuenan Xuan (Emerging Microbes and Infections)
Due to the lack of efficacy of the currently used chemical drugs, poor tick control, and lack of effective vaccines against Babesia, novel control strategies are urgently needed. In this regard, searching for anti-Babesia gene therapy may facilitate the control of this infection. Following this pattern, small interfering RNAs (siRNAs) are widely used to study gene function and hence open the way to control the parasite. However, the primary constraint of this approach is the lack of Babesia to RNA-induced silencing complex (RISC) enzymes, making siRNA impractical. In this study, we preassembled complexes with the human enzyme argonaute 2 (hAgo2) and a small interfering RNA (siRNA)/single-stranded RNA (ssRNA) against B. gibsoni and B. microti metabolite transporters. The assembled complexes were generated by developing a gene delivery system with chitosan dehydroascorbic acid nanoparticles. The delivery system effectively protected the loaded RNAi and targeted Babesia-infected RBCs with a relatively high internalization rate. The assembled complexes were successfully transfected into live parasites for specific slicing of Babesia targets. We demonstrated a reduction in the expression of target genes at the mRNA level. Furthermore, this silencing inhibited Babesia growth in vitro and in vivo. For the first time, we used this method to confirm the role of the assembled complexes in manipulating the noncanonical pathway of RNAi in Babesia parasites. This novel method provides a means of silencing Babesia genes to study their role in host–parasite interactions and as potential targets for gene therapy and control.